1990
DOI: 10.1021/bi00494a030
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors directed to binding domains in neutrophil elastase

Abstract: Human neutrophil elastase (HNE) can be inhibited by unsaturated fatty acids, including oleic acid [Ashe, B. M., & Zimmerman, M. (1977) Biochem. Biophys. Res. Commun. 75, 194-199; Cook, L., & Ternai, B. (1988) Biol. Chem. Hoppe-Seyler 369, 627-631], but is not affected by saturated fatty acids. We have shown that the interaction of oleic acid with HNE can be characterized by two apparent inhibitory modes: a high-affinity mode (Ki = 48 +/- 3 nM), resulting in partial noncompetitive inhibition (87% residual activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 55 publications
(56 reference statements)
0
22
0
Order By: Relevance
“…The mutations in the TIMP-3 gene [40] in patients with Sorsby's fundus dystrophy have been identified. Disruption of connective tissue turnover and the consequent effect on matrix stability has been implicated in a number of diseases [26,32,37], and the role of MMPs has been demonstrated in the ECM/MMP/TIMP family [26,32,33,37]. Collectively, these studies suggested that disruption of MMP-mediated matrix remodeling does affect the composition and function of tissues.…”
Section: Extracellular Matrix Dynamics and Genetic Basis Of Heart Faimentioning
confidence: 95%
“…The mutations in the TIMP-3 gene [40] in patients with Sorsby's fundus dystrophy have been identified. Disruption of connective tissue turnover and the consequent effect on matrix stability has been implicated in a number of diseases [26,32,37], and the role of MMPs has been demonstrated in the ECM/MMP/TIMP family [26,32,33,37]. Collectively, these studies suggested that disruption of MMP-mediated matrix remodeling does affect the composition and function of tissues.…”
Section: Extracellular Matrix Dynamics and Genetic Basis Of Heart Faimentioning
confidence: 95%
“…Human neutrophil elastase (HNE) can be One of the most important of these proteases is neutrophil activated by high ionic strength (Lestienne and Bieth 1980) ABBREVIATIONS and is inhibited by a number of polyanionic compounds, including negatively charged polysaccharides (Baici and Bradamante 1984) and RNA (Simon et al 1988). Exarnination of the three-dimensional structure of this protease determined by X-ray crystallography indicates that the extended substrate binding cavity contains abundant hydrophobic side chains and, in the vicinity of the subsites SrSS, a positively charged arginine guanidino group (Arg 217) that has been implicated in binding polyanionic inhibitors (Bode et al 1989; Cook and Ternai 1988; Tyagi and Simon 1990). A recent report identified EDTA as an inhibitor of HNE and suggested that the anionic chelator may bind to at least 1 of the 19 arginine residues in the enzyme (Burnett et al 1988).…”
Section: Introductionmentioning
confidence: 99%
“…The mutations in the TIMP-3 gene [Weber et al, 19941 in patients with Sorsby's fundus dystrophy have been identified. Disruption of connective tissue turnover and the consequent effect on matrix stability has been implicated in a number of diseases [Tyagi and Simon, 1990;Tyagi et al, 1995b, and the role of MMPs has been demonstrated in the ECM/MMP/TIMP family [Tyagi et al, 1995b. Collectively, these studies suggested that disruption of MMP-mediated matrix remodeling does affect the composition and function of tissues.…”
mentioning
confidence: 99%